The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, A.; Roda, F. (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
The following values have no corresponding Zotero field: accession-num: 12670768
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall